Physical Exercise Intensity During Submersion Selectively Affects Executive Functions. (March 2021) - Möller, Fabian; Hoffmann, Uwe; Dalecki, Marc; Dräger, Tobias; Doppelmayr, Michael; Steinberg, Fabian
Objective: The intact cognitive processing capacity in highly demanding and dynamically changing situations (e.g., in extreme environmental conditions) is of central relevance for personal safety. This study therefore investigated whether underwater physical exercise (PE) affected cognitive performance by comparing these effects during underwater fin-swimming as opposed to inactivity under normal environmental conditions. Background: Although acute bouts of PE can modulate cognitive performance under highly controlled and standardized laboratory conditions, no previous study has determined whether PE acutely modulates cognitive performance in non-laboratory testing conditions involving extreme environments (e.g., underwater). Method: A total of 27 healthy volunteers (16 males and 11 females; 28.9 ± 7.4 years of age) participated in two experiments involving either moderate or high PE intensity. A PRE/POST crossover design was employed among participants while performing cognitive tests in a counterbalanced order (i.e., before and after 20 min of PE in submersion [WET] and once before and after inactivity [DRY] while in the laboratory). Cognitive performance was measured as a combination of executive functions through the Eriksen Flanker (inhibition) and Two-Back (working memory) Tasks using an underwater tablet computer. Results: ANOVAs revealed enhanced reaction times only in the Flanker test after moderate PE for the WET condition. No other effects were detected. Conclusion: These findings indicate that cognitive performance is exercise-intensity-dependent with enhanced effects during moderate PE, even in extreme environments (i.e., underwater). Application: These results should be relevant in recreational and occupational contexts involving underwater activity and may also apply to microgravity (e.g., during extra-vehicular activities). Description: This study compared the acute effects of physical exercise (PE) on cognitive performance in an underwater environment while participants fin-swam with SCUBA (self-contained underwater breathing apparatus) gear. Findings revealed that 20 min of moderate PE positively affected cognitive performance (i.e., inhibitory control ability). However, no changes were observed after high-intensity exercise.